Vaping aint' cool - Look, Keyun; Ser, Hooi Leng *; Amar, Daud Iskandar Abdullah *; Elil, Renganathan *; Long, Chiau Ming * (MalaysiaKini, 2023)
The lack of regulation for vaping is a critical concern, especially considering the increasing popularity of cooling flavours vape products among young adults. These flavours may escalate the frequency of vaping and potentially lead to nicotine dependency.